CL Comparative Study between Classical and Molecular Methods in Diagnosis of Leishmania Species in Iraq - Magda Abdel Kalek Ali; Ali Khamesipour; Abdulsadah Rahi; Mehdi Mohebali; Amir Ahmad Akhavan (Journal of Men's Health, 2018)
Background and Objective: Cutaneous leishmaniasis (CL) remains a serious public health concern in some parts of Iraq. The aims of this study to diagnose the Leishmania sp. causative agent of CL in some parts of Iraq, by different parasitological, cultural, and molecular methods. It was carried during the period  October  2014 to  February 2015.